MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI METODE PROYEK DENGAN MENGGUNAKAN BARANG BEKAS DI PAUD BHAKTI KEBUNDURIAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Amreni, Sri; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine the increase in the fine motor skills of children through the activities of the project method, to determine the method of project implementation activities and to find out how high the increase in the fine motor skills of children through the activities of the project method using second-hand goods in PAUD Bhakti Kebundurian. The results of the class action there is an increase compared to before the given action that is 63.1%. That is, using regular and sustainable projects in learning can improve fine motor skills of children aged 5-6 years in early childhood Kebundurian Bhakti.Based on the research results can be summarized as follows: project method can improve fine motor skills of children aged 5-6 years in early childhood Bhakti Kebundurian Kecamatan Gunung Sahilan. Methods project set out to increase the fine motor skills of children aged 5-6 years with implemented two cycles. In the first cycle, the project method executed three meetings, and obtained began developing criteria (MB) to the value of 40.3%, the researchers went to the second cycle. Cycle II held a meeting, and obtained the criteria evolved according to expectations (BSH) with a value of 63.1%. Thus, the study did not proceed to the next cycle. So with the project method can improve fine motor skills of children aged 5-6 years the ECD Bhakti Kebundurian District of Mount Sahilan. The percentage increase in the fine motor skills of children aged 5-6 years using project methods in early childhood Bhakti Kebundurian Kecamatan Gunung Sahilan 56.5% from the first cycle to the second cycle.Key Word: Fine Motor Skill, Project Metode